Transnational digital entrepreneurship and enterprise effectiveness: A micro-foundational perspective - Sufyan Muhammad; Degbey William Y.; Glavee-Geo Richard; Zoogah Baniyelme D. (Elsevier, 2025)
Transnational digital entrepreneurship (TDE), the establishment of digital enterprises by combining home- and host-country value creation to serve domestic and foreign customers, is increasing. In order to understand the role of entrepreneurs in transnational digital enterprise effectiveness, we investigate how the competencies of transnational digital entrepreneurs influence social interactions among stakeholders that contribute to enterprise effectiveness. We apply the micro-foundations perspective of management and entrepreneurship and semi-structured interview data from transnational entrepreneurs from six countries—Finland, Sweden, Norway, New Zealand, Australia, and the USA—and their partners in Pakistan. We find that entrepreneurs’ digital knowledge, skills, and abilities—versatile cognitive capabilities, digital managerial capabilities, and multicultural capabilities—affect social interactions through four socio-structural mechanisms—structural support, trust-building, knowledge sharing, and resource configuration—that enhance enterprise effectiveness. We discuss the theoretical and practical implications for transnational entrepreneurship, policymakers, and migrant entrepreneurs.